PENGARUH KEBIJAKAN UTANG, PROFITABILITAS DAN LIKUIDITAS TERHADAP KEBIJAKAN DIVIDEN DENGAN SIZE SEBAGAI VARIABEL MODERASI PADA SEKTOR MANUFAKTUR PERIODE 2008-2011 - Sunarya, Devi Hoei (University of Surabaya, 2013)
This study aims to analyze the factors that influence dividend policy in Manufacturing sector, both in big companies and small companies, which is listed on the Indonesia Stock Exchange during the period 2008-2011. Variable used is debt policy, profitability and liquidity. Number of companies used in this study is 26 companies. This study uses quantitative approach with multiple linier regression method. This study found that in Manufacturing Sector since 2008 up to 2011; debt policies, profitability and liquidity are simultaneous significantly affect dividend policy. Partially, debt policies, profitability and liquidity are significantly affect dividend policy. But, the variable of interaction of debt policies with dummy size, the variable of interaction of profitability with dummy size, and the variable of interaction of liquidity with dummy size are not significantly affect dividend policy.